Alteration of mitochondrial protein complexes in relation to metabolic regulation under short-term oxidative stress in Arabidopsis seedlings. - Obata, T; Matthes, A; Koszior, S; Lehmann, M; Araújo, W; Bock, R; Sweetlove, L; Fernie, A (2011)
Plants reconfigure their metabolic network under stress conditions. Changes of mitochondrial metabolism such as tricarboxylic acid (TCA) cycle and amino acid metabolism are reported in Arabidopsis roots but the exact molecular basis underlying this remains unknown. We here hypothesise the reassembly of enzyme protein complexes to be a molecular mechanism for metabolic regulation and tried in the present study to find out mitochondrial protein complexes which change their composition under oxidative stress by the combinatorial approach of proteomics and metabolomics. Arabidopsis seedlings were treated with menadione to induce oxidative stress. The inhibition of several TCA cycle enzymes and the oxidised NADPH pool indicated the onset of oxidative stress. In blue native/SDS-PAGE analysis of mitochondrial protein complexes the intensities of 18 spots increased and those of 13 spots decreased in menadione treated samples suggesting these proteins associate with, or dissociate from, protein complexes. Some spots were identified as metabolic enzymes related to central carbon metabolism such as malic enzyme, glyceraldehyde-3-phosphate dehydrogenase, monodehydroascorbate reductase and alanine aminotransferase. The change in spot intensity was not directly correlated to the total enzyme activity and mRNA level of the corresponding enzyme but closely related to the metabolite profile, suggesting the metabolism is regulated under oxidative stress at a higher level than translation. These results are somewhat preliminary but suggest the regulation of the TCA cycle, glycolysis, ascorbate and amino acid metabolism by reassembly of plant enzyme complexes.